Predictors of Locoregional Recurrence in Oral Squamous Cell Carcinoma (Update Dental College Journal, 2022)
Introduction: Lip and oral cavity cancer is the third and fifth most frequent cancer for men & women respectively in Bangladesh. Locoregional recurrence after primary surgery is common for oral cancer due to aggressive local invasion and metastasis. The objective of this study was to analyze the predictors of locoregional failure in a tertiary center hospital.Materials and Methods: A prospective cohort study was designed to analyze the presence of recurrences of OSCC patients after surgery. The purposive sampling technique was used to include patients in the study. Excision of the primary tumor was done with neck dissection followed by reconstruction with local or regional flap. The variables considered were demographic information, site, TNM stage at diagnosis, margin status, lymph node metastasis, perineural invasion, recurrence, and the adjuvant therapy used for disease control. Patients were followed up by hospital revisits or phone calls and necessary information was collected through a standardized data collection sheet.  Results: A total of 39 patients were included for data analysis. The male to female ratio was 1:2 and the most common primary site was mandibular alveolar mucosa (31%). Nearly 90% of patients were admitted with stage ׀׀׀ or ׀ᴠ lesions and tumor margin was positive in 21% of cases. Lymph node metastasis and perineural invasion were identified in 64% and 23% of cases respectively. Recurrence developed in 14 patients (36%) during the average follow-up of 13 months. Recurrences were more common in females (42%) and Postoperative histopathology showed a positive margin, perineural invasion, and N3 neck node. Univariate logistic regression analysis for locoregional recurrence showed no significant association between the variables and recurrence. Patients with clinically palpable lymph node, grade 2 lesion, presence of perineural invasion, presence of co-morbidity, patients who did not receive any adjuvant therapy, and patients who had metastatic neck node showed an increased odds ratio (OR>1).Conclusion: The clinicopathologic and treatment-related factors of recurrence in OSCC were explored in this study. Although no significant association was identified between the variables and recurrence of lesions, a high recurrence rate was observed in a shorter span of the follow-up period.Update Dent. Coll. j: 2022; 12 (1): 12-16